Coronary Artery Anomalies: the Efficiency in Diagnosis by the Improved Method in Autopsy Material - Boiko O.; Maksymchuk E. (Львівський клінічний вісник)
Introduction. Coronary arteries anomalies can only be found during the pathomorphololgical detailed study because clinical symptoms are often absent. The coronary artery anomalies are classified as anomalies of origination, course, quantity, permeability and communication. However, these variants of coronary artery anomalies can be missed unless a careful search with macro and microscopic examinations and preparation. Purpose of the research. To find out the efficiency of an improved method in diagnosis of coronary artery anomalies in autopsy material. Materials and research methods. The improved method of diagnosis of coronary artery anomalies in autopsy material was taken to get the quality image of angioarchitectonics of coronary arteries by correcting the components of pouring mass which does not damage the vascular wall, to use the angiography, to improve the histological tissue techniques for histopathological study of coronary arteries, to establish the diagnosis. The autopsies were performed by the improved method at Lviv Regional Pathology Bureau. The pouring mass contained “Triombrastum” (manufacturer Farmak JSC, Ukraine), methylene blue and gelatine and was injected into the coronary arteries. Thereafter the angiographic studies of coronary arteries were performed. The histological specimens of vascular wall were examined by the light microscopy. Results of the investigation and their discussion. The improved method of diagnosis of the coronary artery anomalies in autopsy material was carried out in the following stages. In the first stage the heart was removed during the autopsy. The coronary arteries were injected by the pouring mass. In the second stage the heart was carried to a standard dental x-ray film in size of 305×405 mm. Angiographic studies were performed on the high-frequency dental X-ray unit “PLANMECA Intra” (manufacturer PLANMECA OY, Finland). In the third stage the sections of vascular wall were completed, followed by the painting of them according to standard histological and histochemical methods. The proposed method allows tincturing the sections of vessel wall with the help of standard histological and histochemical techniques after angiographic studies, to explore the postmortem changes of the coronary arteries, to detect the coronary arteries anomalies that is extremely important for the pathomorphological diagnosis and explains the cause of myocardial ischemia. Conclusions. The improved method of diagnosis of coronary artery anomalies in autopsy material is effective and can be used in the practice of pathology.